2019
DOI: 10.1111/cpf.12596
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic training session length affects arterial elasticity

Abstract: Purpose The purpose of this study was to examine haemodynamic and arterial elasticity responses to aerobic exercise of varying durations. Methods Eighteen male subjects (age = 23Á4 AE 2Á0) performed a maximal aerobic fitness (VO 2max ) test. Participants met in the laboratory following an overnight fast for three randomly assigned sessions. Assessments for large and small arterial elasticity (SAE), systemic vascular resistance (SVR), total vascular impedance (TVI), systolic blood pressure (SBP), diastolic bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 29 publications
3
9
0
Order By: Relevance
“…The significant increases seen in SAE after the 60min session are similar to those reported by Karabulut et al (19) who investigated how arterial elasticity would respond to different lengths of an aerobic exercise session. They compared 30, 45, and 60 minutes of aerobic exercise at 65% V̇ o 2 max to see which protocol would elicit greater responses in arterial elasticity.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The significant increases seen in SAE after the 60min session are similar to those reported by Karabulut et al (19) who investigated how arterial elasticity would respond to different lengths of an aerobic exercise session. They compared 30, 45, and 60 minutes of aerobic exercise at 65% V̇ o 2 max to see which protocol would elicit greater responses in arterial elasticity.…”
Section: Discussionsupporting
confidence: 86%
“…This training method requires shorter exercise durations (∼10–20 minutes) and lower intensities (20–50% of 1 repetition maximum or V̇ o 2 max) to elicit these improvements compared with recommended traditional training protocols. Because a recent finding suggested that a 60-minute bout of traditional aerobic exercise may be necessary to significantly improve small arterial health (19), and lack of time is one of the most common obstacles to engage in physical activity, it would be valuable to investigate the efficacy of BFR training on arterial elasticity. If BFR training shows comparable changes in the cardiovascular system to those seen after moderate- or vigorous-intensity and long-duration exercise, this alternative training approach with shorter session time may motivate many people to start engaging in regular physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, exercise duration prescriptions via fixed absolute values, such as (20, 30, 45, 60, 90 min, etc. per session or per day), as usually applied in training practice and scientific studies (Diment et al, 2015 ; Karabulut et al, 2020 ; Myllymäki et al, 2012 ; Tremblay et al, 2005 ; Viru et al, 1996 ), may result in undesired and heterogeneous acute responses and training effects such as overreaching /overtraining or the nonresponder phenomenon (Lin et al, 2021 ; Ross et al, 2015 ), which makes it difficult or even impossible to compare studies. In addition, exercise with a too‐long total duration for a given intensity (near t max ) may lead to health risks, particularly in patients (Mezzani et al, 2010 , 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tremblay et al ( 2005 ) critically mentioned that only a little research tempting to isolate the effects of exercise duration has been done. Some studies showed an exercise duration dependency for manifold physiologic effects during and/or after exercise such as muscular micro RNA release that controls posttranscriptional gene expression (Ramos et al, 2018 ), hormone release (Tremblay et al, 2005 ; Viru, 1995 ; Viru et al, 1996 ), hemodynamic and arterial elasticity and total vascular resistance (Karabulut et al, 2020 ), nocturnal heart rate (HR) and heart rate variability (HRV) (Myllymäki et al, 2012 ), excess postexercise oxygen consumption and metabolism (Bahr et al, 1987 ; Chad & Wenger, 1985 , 1988 ; Gore & Withers, 1990a , b ; Sedlock et al, 1989 ), as well as immune response (Diment et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the early studies used a single, acute bout of the exercise to explore various physiological responses and then imply that the lower intensity protocols used with blood flow restriction (20–30% 1RM) were as effective as high-intensity (80% 1RM) resistance exercise for gaining strength and promoting muscle hypertrophy. Training protocols using blood flow restriction are fairly limited and usually short in duration, normally lasting between 4 and 8weeks ( Clark et al, 2011 ; Cook et al, 2014 ; Conceição et al, 2018 ; Held et al, 2020 ; Karabulut et al, 2020 ; Zhao et al, 2020 ). Most often, training protocols use 3 training sessions per week with each session separated by 48h ( Clark et al, 2011 ; Held et al, 2020 ) but some designs use daily bouts of exercise (5 times per week) and some even use 2 bouts per day for 8 to 10 consecutive days ( Iida et al, 2006 ).…”
Section: Anaerobic Exercises With Blood Flow Restrictionmentioning
confidence: 99%